TINJAUAN PERENCANAAN SALURAN SEKUNDER DAERAH IRIGASI MONTANG KECAMATAN NARMADA KABUPATEN LOMBOK BARAT - Andreas Kanda Wonda; Muhamad Yamin; Aminullah Aminullah (LPPM PSDKU Kampus Mataram UNMAS Denpasar, 2021)
The purpose of this study is to describe whether the current available discharge is able to irrigate rice fields and the dimensions of irrigation channels needed for the welfare of farmers in Montang Village with the existing channel system. This type of research is a case study research with a quantitative approach. The results of this study indicate that: 1) The minimum maximum need for irrigation water (DR) through tertiary channels in Montang Village is 11,364 l / sec / ha, which means that it is able to irrigate rice fields. 2) Dimensions of the Montang irrigation channel consisting of 2 main channels and 4 primary channels, from the four substrate channels each is obtained for the left secondary channel where: channel width 2.0 m water depth 2.0 m with 0.85 m high guard while the right secondary channel obtained a channel width of 2.0 m, water depth of 2.0 m and 0.85 m height of guard.